Personal Hygiene Behavior of Adolescent Girls is Related to the Incidence of Vaginal Discharge: Perilaku Personal Hygiene Remaja Putri Berhubungan Dengan Kejadian Keputihan - Narmin, Narmin; Taqwin, Taqwin; Pani, Widya; Hasnawati, Hasnawati; Lisnawati, Lisnawati; Putri, Ananda Avifa (Poltekkes Kemenkes Palu, 2024)
Background: Teenage girls often do not maintain their hygiene, because they consider vaginal discharge as unimportant. Interviews conducted with 10 female students at SMPN 18 Palu found that they had experienced vaginal discharge but did not know about the causes and impacts of vaginal discharge. Purpose: The relationship between the personal hygiene behavior of adolescent girls and the incidence of vaginal discharge at SMPN 18 Palu is known. Methods: This study is an analytical survey with a cross-sectional approach. The study involved 57 female adolescents using the proportionate stratified random sampling technique. The study was conducted in April-May 2024 and the data collection tool was a questionnaire. The Chi-Square test was used to analyze the data. Results: As many as 28 respondents (49.1%) had adequate personal hygiene behavior and 43 respondents (75.4%) experienced vaginal discharge. The Chi-Square test results obtained a p-value of 0.027 (<0.05). Conclusion: There is a relationship between the personal hygiene behavior of adolescent girls with the incidence of vaginal discharge at SMP Negeri 18 Palu. Health workers are advised to provide education about personal hygiene to prevent vaginal discharge in every school